Actaticas A−G, Cycloartane Triterpenes From Actaea asiatica With Their Antiproliferative Activity - Hu, Meigeng; Zhao, Dan; Xu, Xudong; Ma, Guoxu; Wu, Haifeng; Chen, Xi (Frontiers in Chemistry, 2021)
Phytochemical studies on the rhizomes of Actaea asiatica led to the isolation of seven new cycloartane triterpenes, actaticas A−G (1−7). Their structures were determined by NMR, HRESIMS, and chemical analysis. All the isolates were evaluated for their antiproliferative activity against HT-29 and McF-7 cell lines. The results showed that all the compounds displayed cytotoxicity. All compounds showed significant inhibitory effects with IC50 values of 9.2–26.4 μM.